Adopting America childhood, kinship, and national identity in literature - Singley, Carol J., 1951- (New York ; Oxford : Oxford University Press, 2011)
American literature abounds with orphans who experience adoption or placements that resemble adoption. These stories do more than recount adventures of children living away from home. They tell an American story of family and national identity.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: American literature -- History and criticism; Families in literature; Adoption in literature; National characteristics, American, in literature; Children in literature